Urban nature and transnational lives. Issue 4 (10th December 2020) - Rishbeth, Clare; Birch, Jo
Abstract: This paper explores ways in which first generation migrants living in a UK city engage with urban nature. Through understanding mundane connections with local nature (plants, animals and seasons), we attend to two questions 'what can narratives of urban nature tell us about experiences of migration', and inversely 'what can diverse migrant voices tell us about experiences of urban nature'? We draw on interview data with 23 participants, all born overseas, with a diverse mix in terms of age (young adults to older retired people), gender, country of origin and length of time resident in the United Kingdom. The analysis focuses on three areas: multisensory engagements with weather, care for nature and how transnational identities surface through the relational dimensions of nature narratives. We conclude by highlighting the potential of embodied nature engagement to support a sense of wellbeing and transnational identity across the life‐course, with potential to more broadly reflect pluralist understandings of the urban environment.